Motivasi Guru Pendidikan Islam Perspektif Maslow's Hierarchy of Needs - Hidayati; Yolanda Lupita Sary (Jurnal Tahdzibi: Manajemen Pendidikan Islam, 2026)
This study is motivated by the declining work motivation of Islamic education teachers, influenced by limited welfare, increasing professional demands, and the lack of integration between psychological approaches and spiritual values in understanding motivation. This study aims to analyze teacher motivation in Islamic education through Maslow’s hierarchy of needs and to construct its integration with Islamic values. The research employs a qualitative approach using a library research design, with data sources consisting of scholarly books, journal articles, and relevant academic documents. The research instrument is the researcher, with data collected through systematic literature review and analyzed using content analysis techniques. The findings indicate that Maslow’s theory effectively explains the structured needs of teachers; however, it requires reinterpretation through Islamic spiritual values such as intention, sincerity, and worship orientation. This integration produces a more holistic motivational framework that encompasses not only the fulfillment of needs but also meaning and transcendental purpose. The study concludes that teacher motivation in Islamic education is a multidimensional construct that requires an integrative approach to be more contextual and applicable in educational practice.